The Influence of Tiktok on Students’ Perception in Narrative Text Learning for Vocational HighSchool - Nadhilah, Ummi (RETAIN : Journal of Research in English Language Teaching, 2023)
One of the most difficult functional texts for students to learn is narrative text. Perception has an important role in learning success because someone will accept and support the perceived object if they have a positive perception. Analyzing Tiktok's influence on students' perceptions of narrative text learning is the goal of this study. A pre-experimental, one-group pretest-posttest design was used in this study. 35 students from the X grade at one of the public vocational schools in Mojoagung, Jombang, were selected as the study's sample. Pre-post test with four indicators distributed to obtain data from respondents. The findings in this study showed a significant influence of the Tiktok application on students' perceptions of narrative text learning, with a Significance value of 0,000. In addition, the results of this study also show that the Tiktok application can increase student confidence, motivation, and interest in learning narrative texts. In addition, the Tiktok application also affects students' emotions positively, so it can help with understanding narrative text.